Sistem Penunjang Keputusan Dengan Menggunakan Metode Ahp Dalam Seleksi Produk - Musli Yanto (Prodi Sistem Informasi Universitas Dharma Andalas, 2021)
Decision Support Sistem Is A Concept That Can Be Applied To Help Humans In Decision Making. In this research, the problem that will be faced is how the process of determining or selecting a product that is most interested in a mini market by adopting the concept of a decision support sistem. The method to be used is the Analytical Hierarchy Process (AHP). This method is able to provide results in the form of number results from the selection process, the results given later will also give the calculation results of the criteria. The Criteria Are Price, Taste, Product Design, Aroma And Benefits. Based on the results obtained that the price has a priority value of 30-50%. The purpose of this study is to help the mini market to see which products are interested. Then the benefits obtained are to assist the Mini Market Manager to provide products of interest so that there is no accumulation of products resulting in losses